Clinical Profile and Non-invasive Predictors of Fibrosis in a Newly Diagnosed Non-Alcoholic Fatty Liver Disease Patient in a Tertiary Health Care Center of Nepal - Koirala, Dinesh; Pathak, Rahul; Kafle, Brindeswari; Jha, Anurag; Hamal, Rabin; Gnawali, Arun; Pandey, Rajesh; Bhusal, Mohan; Gyawali, Susmita (Bangladesh Medical Journal, 2024)
Non-Alcoholic Fatty Liver Disease (NAFLD) represents a spectrum of histopathologic abnormalities ranging from simple steatosis to the more aggressive non-alcoholic steatohepatitis, characterized by steatosis, parenchymal inflammation, hepatocellular ballooning and other evidence of hepatic injury. The objective of this study is to evaluate the demographic and anthropometric profile of non-alcoholic fatty liver disease and non-invasive predictors of fibrosis. This is a hospital-based observational study. A total of 280 patients were included in this study from the Department of Gastroenterology, Tribhuvan University Teaching Hospital from January 2019 to August 2021 were included. Patients presenting with non-alcoholic fatty liver disease were mostly (29.64%) of 36-45 age group. Two-third of the patients (66.78%) were asymptomatic. The mean body mass index of patients was 28.10±4.10 kg/m2 and most of them (81.07%) had body mass index >25 kg/m2. More than one third of the patients (40%) with non-alcoholic fatty liver disease had presence of metabolic syndrome. The mean (±SD) ultrasound attenuation parameter was 284.22±31.58 dB/m. Fatty liver index showed a positive and a medium strength correlation with fatty liver. On Spearman rank correlation, ultrasound attenuation parameter steatosis grading was correlated positively and strongly with the USG grading of fatty liver (p<0.001). On Pearson correlation, APRI, NFS and FIB-4 were positive but weakly correlated with liver stiffness measurement by FibroTouch but still the correlation was statistically significant (p<0.01). Fatty liver index has shown a good correlation with the presence of steatosis by a FibroTouch. Similarly, APRI showed the highest correlation in predicting liver stiffness in the population of Nepal. Other multicenter large scale prospective analytical studies would be required for further clarify of the results of such a kind of research. Bangladesh Med J. 2023 Sept; 52(3): 35-40